Analysis of the reaction forces during circles execution on a gymnastic mushroom - Ferrer, V.; Turmo, A. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Men's gymnastics is comprised of six events, all of them produce loadings to the upper extremity but specifically, the pommel horse demands repetitive and high intensity wrist impacts on a rigid structure, with sustained periods of body weight support on the wrist (Marklof et al, 1989). In a study of elite male gymnasts (Mandelbaun et al., 1989) the pommel horse was the apparatus associated with the most wrist pain. Most of the gymnasts begin at a young age to do this sport, therefore their wrist growth plate is a zone with critical injury options. The purpose of this study was to measure the force applied by the gymnasts during the execution of circles on a mushroom apparatus used to improve techniques of the pommel horse.